Anxiety Judging from Self-Acceptance and Social Support in Adolescent with Blind/ Kecemasan Ditinjau dari Penerimaan Diri dan Dukungan Sosial pada Remaja Penyandang Tunanetra - Liedya, Liedya; Br Tarigan, Sri Mariati; Justio, Elbert; Novina, Tiffany; Marpaung, Winida (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
Blind people's limitations affect their movement development, learning ability, and psychological development because of the difficulty of understanding and accepting the surrounding environmental conditions. This study aims to examine the relationship between self-acceptance and social support with anxiety. The hypothesis of this research was there is a relationship between self-acceptance and social support with anxiety. Subjects in this research were 80 blind adolescents in Pertuni Medan Foundation. Data analysis used is Multiple Linear Analysis through the help of SPSS 25 for Windows. Data analysis results showed that there is no relationship between self-acceptance and social support with anxiety. Copyright © 2020. Psikoislamika: Jurnal Psikologi dan Psikologi Islam